MODERN CCD OBSERVATIONS OF SELECTED MINOR PLANETS FOR THE CONNECTION OF DYNAMIC AND KINEMATIC COORDINATE SYSTEMS - Pomazan, A.; Maigurova, N. (Одеські астрономічні публікації, 2016)
One of the methods of determining the orientation parameters of the dynamic and kinematic coordinate systems is to use of long-term series of ground-based observations of selected asteroids. For achievement of the best accuracy of the link parameters the high precision and uniformly covering the asteroids orbit observations are necessary. The analysis of the available observations of selected asteroids was made with usage MPC database. The value of the true anomaly at the moment of observation was selected as parameter of orbit covering. It is shown that there are orbital segments without precise observations. This was taken into account when forming the observational list for the telescope KT-50 (Mobitel complex). 1596 positions of 50 asteroid have been obtained during 2014- 2016. The comparison of the calculated positions with ephemeris obtained by on-line service HORIZONS was made. The RMS errors of the differences (O-C) were about 0.1 arcsec for both coordinates. The comparison of the obtained results with observations of the some ground based observatories and Hipparcos satellite shows high accuracy and uniformity of Nikolaev asteroid observations.